About Emergencies Occur at Chemically Hazardous Facilities - Kasimov, A. A. (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses what emergency situations may arise in case of accidents at chemically hazardous facilities (hereinafter HOO) located on the territory of the Republic of Uzbekistan